Answer:
Step-by-step explanation:
In this question, you are combining like terms, meaning doing equations to numbers that fit with only each other.
<u>So we should start on the number without variables:</u>
23 and 27
<u>Match them up together and you should find your first equation:</u>
23 - 7
==> -4
So we should have -4 + 8m + 4n - 5m
Now we should combine the numbers with the variable of m:
8m and 5m
<u>Match them up together and you should find your first equation:</u>
<u></u>
8m - 5m
==> 3m
So we should now have -4 + 3m + 4n
<u></u>
<u>Since there are no other variables of n, we are all done:</u>
<u>-4 + 3m + 4n is your final answer </u>
We cannot simplify it because the denominator does not have a common factor with the numarator.
The answers are
f
o
g
(
x
)
=
−
2
x
+
23
and
g
o
f
(
x
)
=
−
2
x
+
5
Explanation:
f
(
x
)
=
−
2
x
+
11
g
(
x
)
=
x
−
6
f
o
g
(
x
)
=
f
(
g
(
x
)
)
=
f
(
x
−
6
)
=
−
2
(
x
−
6
)
+
11
=
−
2
x
+
12
+
11
=
−
2
x
+
23
g
o
f
(
x
)
=
g
(
f
(
x
)
)
=
g
(
−
2
x
+
11
)
=
−
2
x
+
11
−
6
=
−
2
x
+
5
I think that the equations speak by themselves.
Of course,
f
o
g
(
x
)
≠
g
o
f
(
x
)
Step-by-step explanation:
Let x represent the number.
We have 2x + 18 = 3x - 5, therefore x = 23.
The number is 23.
To calculate the z-statistic, we must first calculate the
standard error.
Standard error is standard deviation divided by the square
root of the population. In this case, it is equal to 2.68.
The z-score is defined the distance from the sample to the
population mean in units of standard error.
z = (195 – 208)/2.68 = -4.86